(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study aims to determine the training needs of Agricultural farm employees in the Davao region. The study aims to identify the Training needs to be implemented in the said company to develop knowledge, skills, attitudes, and other attributes (KSAOs). The industry is facing a fast pace of change. Thus, it comes to an understanding that Training is essential, and the development among the organization members becomes necessary to cope with the intense competition in the market. The study’s findings revealed that Rank-and-File (Non-people Handler) employees of the said company have poor performance issues in terms of Innovation, Quality of Work, Job Knowledge, Accountability, and Attendance. On the other hand, Supervisory to Managerial (People Handler) employees manifested poor performance in terms of Quality of Work, Job Knowledge, Punctuality and Attendance, Planning and Organizing, and Decision-making. The researcher recommends the implementation of job rotation, job enlargement, job enrichment, values development program, proper office etiquettes, and Code of Conduct and Discipline Training or orientation to address the performance issue of Rank-and-File employees. Moreover, it should also implement leadership Training such as goal setting, root-cause analysis, people management, and team building to address the poor performance issue of People Handler employees.